Title- To assess the effectiveness of self-instructional module on knowledge of staff nurses regarding FAST HUGS BID on critically ill patients in tertiary care hospital at Karad - MR. JITENDRA KUMAR , Mahesh B. Chendake , DR. Vaishali R. Mohite, Manisha C. Gholap, Namrata Mohite, Dr.Vinayak Raje , Mahesh B. Chendake. (International Journal of Advanced Science and Technology, 2020)
Background Sir JL Vincent attributes the origins of FAST HUG pneumonic. The WR Vincent and Hatton updated the FAST HUG pneumonic by adding some components and convert it to FAST HUGS BID. Objectives To assess the knowledge of staff nurses regarding FAST HUGS BID on critically ill patients before administration of the self-instructional module. To evaluate the effectiveness of self-instructional module on information of staff of nurses relating to FAST HUGS BID on critically ill patients and to find out the association selected socio-demographic variable and knowledge of staff nurses on FAST HUGS BID of critical ill patient. Methods Evaluative approach used. The Pre - experimental research design used in the study. The setting selected for the present study was the critical care unit at tertiary care hospital at Karad In the current study population comprises of staff nurses working in the intensive care unit at tertiary care hospital. Thirty-three staff nurses selected from tertiary care hospitals at Karad. Results Distribution of demographic variables of staff nurses working in the critical care unit at the tertiary hospital shows 27(81.8%) were between the age group 24-31 years, 2(6.1%) were between the age group 32-39 years, 40-47 years and 48 above each. 11(33.3%) were males, while 22(66.7%) were females. 14(42.4%) staff were GNM, 15(45.5%) staff were B.Sc, 4(12.1%) staff were M.Sc. 24(72.7%) staff nurses were Hindus, 2(6.1) staff nurses were Muslims and, 7(21.2%) staff nurses were Christians. 12(36.4%) staff nurses were married and, 21(63.6%) staff nurses were unmarried. 22(66.7%) staff nurses had 3-5 years of experience, 8(24.2%)nurses had 6-10 years of experience and, 3(9.1%) staff nurses had experience of >20 years. 33(100%) staff nurses received information from hospitals and the Internet. The pretest table depicts that out of 33 staff nurses, 32(97%) staff nurses had a low level of knowledge, and all 33(100%) staff nurses had an adequate level of information about FAST HUGS BID on the critically ill patient after administration of self-instructional module. Hence the data reveals the effectiveness of the self-instructional module. The mean knowledge score of 33 staff nurses during the pretest was 19.8%, whereas it had increased up to 92.5%. Therefore the difference assessed was 72.7% between pretest and post-test. Conclusion So it is concluded that This instructional module is useful. Hence on-going teaching and health education programs can further improve the knowledge of staff nurses.